BREAST HEALTH & HORMONES - K.Samo, Ufaque Batool; Nazir Sandano, Musrat; Mangi, Raheela (Annals of Allied Health Sciences, 2024)
Hormone balance is crucial for breast health, with estrogen, progesterone, testosterone, DHEA, cortisol, thyroid, and Vitamin D playing key roles in breast cancer prevention. Detecting estrogen dominance symptoms is crucial to prevent long-term imbalances. Estriol, the weakest estrogen, is believed to protect against breast cancer by reducing its effects, and using it topically does not increase risk. Estriol, a weak estrogen, inhibits growth in breast tissue, and research in Europe shows no significant increase in breast cancer risk among users of weak estrogens over 50. Estriol, a hormone replacement therapy, has been proven safe for post-menopausal women treated for breast cancer, with studies confirming its protective powers and not increasing breast density. Estriol doesn’t increase breast cancer risks, but long-term unopposed use, possibly exacerbated by synthetic progestins, increases the risk, while early 2000 studies suggest estriol may protect against breast cancer. Henry Lemon, MD, hypothesized that breast cancer patients have low estriol levels compared to more potent estrogens. A clinical trial showed estriol treatment caused remission or tumor arrest in 37% of patients, with minimal side effects. Progesterone, an estrogen balancer, regulates reproductive health, menstrual cycle, and blood sugar levels. It plays a crucial role in breast cancer prevention, preventing estrogen dominance. Aging or stress can cause estrogen levels to drop, while progesterone levels may plummet. Adequate progesterone levels in breast cancer patients improve survival chances. Progesterone regulates estrogen levels, causing symptoms like breast stimulation, increased body fat, depression, headaches, and increased risk of endometrial and breast cancer. This natural supplement supports healthy uterine lining, protects against fibrocystic breasts, aids energy use, normalizes blood clotting, prevents endometrial and breast cancer, and balances estrogen and progesterone during menopause. Testosterone, an androgenic hormone, is essential for women’s health, but menopause leads to decreased levels, affecting libido, sexual function, muscle growth, bone renewal, and breast health. Androgen deficiency symptoms include depression, vaginal dryness, and androgen dominance. Drs. Lee and Zava suggest elevated testosterone levels in women may be due to hormonal imbalances caused by menopausal estrogen dominance and lack of progesterone, disrupting the normal circadian rhythm. Cortisol imbalance can cause fatigue, allergies, anxiety, and eating disorders, leading to chronic illness, autoimmune disease, premature aging, and breast cancer risk, especially in women. Thyroid hormone regulates metabolic rates, causing weight gain, depression, low energy, and cold intolerance. Hypothyroidism, prevalent in women during perimenopausal and postmenopausal years, increases breast cancer risk and necessitates thyroid supplements. High estrogen levels increase breast cancer risk in women, while natural progesterone therapy restores thyroid activity. Vitamin D deficiency, prevalent in the elderly, northern climates, and indoors, increases cancer risk in colon, pancreas, prostate, ovaries, and breast, with higher latitudes causing more deaths. Vitamin D deficiency affects darker skin, obesity, and younger children. Frequent sun exposure, cod liver oil intake, and milk consumption can reduce breast cancer risk by 35% in teen and early adulthood. Vitamin D intake reduces cancer risk, but recommended daily allowances are inadequate. Vitamin D deficiency increases cancer risk by 35-50%.